Cover Feature: Crystallographic Visualization of a Double Water Molecule Addition on a Pt1‐MOF during the Low‐temperature Water‐Gas Shift Reaction (ChemCatChem 4/2021). Issue 4 (18th February 2021) - Bilanin, Cristina; Tiburcio, Estefanía; Ferrando‐Soria, Jesús; Armentano, Donatella; Leyva‐Pérez, Antonio; Pardo, Emilio
Abstract : The Cover Feature shows the presence of Pt1  single atoms,  within the channels of a metal‐organic framework (MOF),  which are capable of catalyzing, at low temperature, the water‐gas‐shift reaction (WGSR). In their Full Paper, C. Bilanin et al. show evidence that a double water attack occurs in the Pt‐catalyzed low‐temperature WGSR by a combination of reactivity experiments with soluble Pt catalysts, kinetic and spectroscopic measurements, and operando single crystal X‐ray diffraction on the Pt1 ‐MOF, which constitute a clear step forward on the understanding of the mechanism of the WGSR. More information can be found in the Full Paper by C. Bilanin et al.